Being Other Than We Are... (1st June 2019) - Barnett, Heather
For a number of years, artist Heather Barnett has challenged groups of people to test their capacity for collective action against that of a single celled organism. The experiment, Being Slime Mould, invites a group of humans to operate as a superorganism, taskedwith some fundamental ontological rules of a nonhuman intelligent life form through playful participation.Being (or becoming) slime mould is of course an impossibility; we can no more become slime mould than we can become badger or bat. The point of the exercise, therefore, is in the trying: the endeavour to put aside human ego and individualism in order to shift perception towards other ways of sensing, knowing and being. Drawing on Barnett's own artistic practice, and from the fields of ecology, philosophy and speculative design, this paper investigates the motivations and methods of humans to engage philosophically and experientially with the sensory subjectivities of ontological others.